The impact of Google Scholar on the Indian Journal of Animal Nutrition - Kumar, Dr.Kutty; P. Ramesh Babu; B.V. Subramanyam (Indian Journal of Animal Nutrition, 2023)
Between 1985 and 2021, a Scientometric study of the Indian Journal of Animal Nutrition (IJAN) was conducted using the Publish or Perish (PoP) software platform. (37 Years). The impact of IJAN on current scholarship was determined by mining raw data from Google Scholar and applying 19 citation indicators to it. Zipf’s Law examined annual contributions, authorship patterns, and author productivity trends in 940 scholarly publications. IJAN’s relative growth rate and doubling time were also examined during the study period. According to our information, the year 2003 saw the most publications (38, or 4.04% of the total). The averaged impact rankings of IJAN that were examined are as follows. The present study was based on data from, Indexes (h and g), h-index, g-index, papers, citations, years, citations year, citations paper, citations author, papers author, authors paper, and so on. Index (hc), index (hi), index (hi, norm), index (aw), index (aw), index (aw), index (aw), index (aw), index (aw), index (aw), index (aw), index (aw), index (aw), index (aw), Authors worked together at a rate of 0.99%. (out of a maximum of 1). The study recommends a group practice of journal and author productivity using Zipf’s Law for a more qualitative evaluation of research impact and academic output.